Laparoscopic ileal ureteral replacement to preserve the natural anti‐reflux system: An initial case report. Issue 3 (16th February 2021) - Shinohara, Mayuka; Shin, Toshitaka; Shibuya, Tadamasa; Ando, Tadasuke; Mimata, Hiromitsu
Abstract : Introduction: Ileal ureteral replacement is one of the treatment options for long ureteral strictures. Most ileal ureteral replacements anastomose the distal side of the ileal segment directly to the bladder. We have reported here an initial case of laparoscopic ileal ureteral replacement for preserving the natural anti‐reflux system. Case presentation: A 29‐year‐old male presented with right flank pain, and his imaging results revealed multiple strictures of the right upper‐middle ureter. Hence, we performed a laparoscopic ileal ureteral replacement surgery. The normal distal ureter was preserved, and the distal side of the ileal segment was anastomosed to it. As such, the natural anti‐reflux system could be completely preserved. Following this, the renal function was maintained, and no urinary tract infection was recorded. Conclusion: Laparoscopic ileal ureteral replacement, which preserves the natural anti‐reflux system, can be considered as a treatment option for refractory upper‐middle ureteral strictures.